Directed Differentiation of Human Induced Pluripotent Stem Cells into Dendritic Cells Displaying Tolerogenic Properties and Resembling the CD141+ Subset - Sachamitr, Patty; Leishman, Alison J.; Davies, Timothy J.; Fairchild, Paul J. (Frontiers in Immunology, 2018)
The advent of induced pluripotent stem cells (iPSCs) has begun to revolutionize cell therapy by providing a convenient source of rare cell types not normally available from patients in sufficient numbers for therapeutic purposes. In particular, the development of protocols for the differentiation of populations of leukocytes as diverse as naïve T cells, macrophages and Natural Killer (NK) cells provides opportunities for their scale-up and quality control prior to administration. One population of leukocytes whose therapeutic potential has yet to be explored is the subset of conventional dendritic cells (DCs) defined by their surface expression of CD141. While these cells stimulate cytotoxic T cells in response to inflammation through the cross-presentation of viral and tumor-associated antigens in an MHC class I-restricted manner, under steady-state conditions, CD141+ DCs resident in interstitial tissues are focused on the maintenance of homeostasis through the induction of tolerance to local antigens. Here we describe protocols for the directed differentiation of human iPSCs into a mixed population of CD11c+ DCs through the spontaneous formation of embryoid bodies and exposure to a cocktail of growth factors, the scheduled withdrawal of which serves to guide the process of differentiation. Furthermore, we describe the enrichment of DCs expressing CD141 through depletion of CD1c+ cells, thereby obtaining a population of ‘untouched’ DCs unaffected by cross-linking of surface CD141. The resulting cells display characteristic phagocytic and endocytic capacity and acquire an immunostimulatory phenotype following exposure to inflammatory cytokines and TLR agonists. Nevertheless, under steady-state conditions, these cells share some of the tolerogenic properties of tissue-resident CD141+ DCs, which may be further reinforced by exposure to a range of pharmacological agents including IL-10, rapamycin, dexamethasone and 1,25-dihydoxyvitamin D3. Our protocols therefore provide access to a novel source of DCs analogous to the CD141+ subset under steady-state conditions in vivo and may, therefore, find utility in the treatment of a range of disease states requiring the establishment of immunological tolerance.